FIXED ASSET MANAGEMENT: THE IMPACT ON FIXED ASSETS INTERNAL CONTROL IN INSTITUTIONS OF HIGHER EDUCATION (CASE STUDY: UNIVERSITY DUTA BANGSA SURAKARTA) - Ety Meikhati; Rita Wahyuningsih (LPPM Universitas Duta Bangsa Surakarta, 2022)
Implementation tridharma in institutions of higher education, increase management and service academic no can free from importance availability asset permanent in the form of means adequate infrastructure. The more develop college tall the more increase in assets still owned, so need attention in form management ordinary assets, known with term management asset. Many still consider management asset by physique only just a management tool list asset. This study aims to determine impact implementation management asset to internal control system for fixed assets at Duta Bangsa University Surakarta. The research method used in this study is a qualitative approach with a descriptive method. The data collection technique used is by means of observation and interviews in order to obtain accurate information from the source . The results of the research show that fixed asset internal control it's been going well, where factor supporter in implementation management asset through management asset already have orderly procedure, clear flowchart, adequate human resources as well as device supporter in the form of SINAPRA (System Infrastructure) integrated start from Request fixed asset, procurement fixed asset until with placement fixed asset all via SINAPRA. However implementation still less than optimal because management asset still experience gap on Step implementation procurement asset permanent because condition certain and the need improvement as well as upgrade system to match with provision and needs due to the transfer process placement asset as part from development land Universitas Duta Bangsa Surakarta.